Icevaning control of an Arctic offshore vessel and its experimental validation - Kim, Young-Shik; Kim, Jinwhan (International journal of naval architecture and ocean engineering, 2021)
Managing with the presence of sea ice is the primary challenge in the operation of floating platforms in the Arctic region. It is widely accepted that offshore structures operating in Arctic conditions need station-keeping methods as well as ice management by icebreakers. Dynamic Positioning (DP) is one of the station-keeping methods that can provide mobility and flexibility in marine operations. The presence of sea ice generates complex external forces and moments acting on the vessel, which need to be counteracted by the DP system. In this paper, an icevaning control algorithm is proposed that enables Arctic offshore vessels to perform DP operations. The proposed icevaning control enables each vessel to be oriented toward the direction of the mean environmental force induced by ice drifting so as to improve the operational safety and reduce the overall thruster power consumption by having minimum external disturbances naturally. A mathematical model of an Arctic offshore vessel is summarized for the development of the new icevaning control algorithm. To determine the icevaning action of the Arctic offshore vessel without any measurements and estimation of ice conditions including ice drift, task and null space are defined in the vessel model, and the control law is formulated in the task space. A backstepping technique is utilized to handle the nonlinearity of the Arctic offshore vessel’s dynamic model, and the Lyapunov stability theory is applied to guarantee the stability of the proposed icevaning control algorithm. Experiments are conducted in the ice tank of the Korea Research Institute of Ships and Ocean Engineering to demonstrate the feasibility of the proposed approach.